Roe v. Wade: fifty years after - De Londras, Fiona (History in the headlines, 2024)
On June 24, 2022, Roe v. Wade was shockingly reversed by the Supreme Court. What happened? What transpired socially, politically, legally, in religious institutions and in popular culture in the half-century when ""the right to choose"" led to this stunning transformation in American society?